1976
DOI: 10.1111/j.1744-7348.1976.tb00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Some factors affecting the control of Rhizoctonia solani by systemic and non‐systemic fungicides

Abstract: In laboratory tests, Rhizoctmia solani grew best on agar at 30 "C and pH 5-5. Mycelial growth was strongly inhibited by benomyl, chloroneb and quintozene, less so by thiophanate-methyl. The optimum temperature for inhibition was 25 "C for quintozene; the other three fungicides gave greatest inhibition at the lowest temperature tested (20 "C). Benomyl and thiophanate-methyl were most inhibitory at pH 7-8, chloroneb and quintozene at pH 5-6.In pot trials using mung bean, long melon, egg-plant, common pea and sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Rancona Dimension at the high rate showed the strongest fungitoxic activity against R. solani, not only reducing the severity of root disease but also providing significantly greater protection for dry shoot and root weight and also root and shoot lengths from reductions. While this fungicide showed high efficacy in both river sand and Gingin loam soil, its effect was overall greatest in river sand compared with the loam soil, a similar finding as reported with earlier studies on R. solani by Blair (1943), Kataria and Grover (1976) and Rushdi and Jeffers (1956). Such differences could be a consequence of the lesser absorptive and cation exchange capacity of a sand compared with a loam soil, as demonstrated in past studies relating to the effect of various factors on the degree of control of R. solani with fungicides (e.g., Rushdi and Jeffers, 1956).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Rancona Dimension at the high rate showed the strongest fungitoxic activity against R. solani, not only reducing the severity of root disease but also providing significantly greater protection for dry shoot and root weight and also root and shoot lengths from reductions. While this fungicide showed high efficacy in both river sand and Gingin loam soil, its effect was overall greatest in river sand compared with the loam soil, a similar finding as reported with earlier studies on R. solani by Blair (1943), Kataria and Grover (1976) and Rushdi and Jeffers (1956). Such differences could be a consequence of the lesser absorptive and cation exchange capacity of a sand compared with a loam soil, as demonstrated in past studies relating to the effect of various factors on the degree of control of R. solani with fungicides (e.g., Rushdi and Jeffers, 1956).…”
supporting
confidence: 85%
“…It is noteworthy that there was a significant interaction between the efficacies of fungicides with soil type, highlighting that the greatest potential for new fungicides is particularly likely to be in wheat growing areas where sandy soils rather than sandy loam soils predominate. It is well known that efficacy of fungicides is affected by soil type (Kataria and Grover, 1976;Rushdi and Jeffers, 1956) and specifically so in relation to fungicides affecting root diseases caused by R. solani (e.g., Bateman, 1984;Bateman andNichols, 1982: Bateman et al, 2008;Cook et al, 1987;Ebbels, 1969). In particular, the study of Kataria and Grover (1976) observed that the fungicides benomyl, thiophanate-methyl, chloroneb and quintozene were more effective in a sandy loam than in a loam or clay loam soil, despite approximately similar disease incidence/severity in these three soil types.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although severe RRR in beans has been often observed in wet soils (Kataria and Grover ; Kobriger and Hagedorn ; Allen and Lenné ), there are a few reports on the best growth of R. solani at low soil moisture content (Blair ; Sneh et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The method for inoculating the soil (autoclaved) was the same as reported earlier (Kataria & Grover, 1976). One kg soil was packed into a 15 cm diameter earthenware pot into which seeds were sown.…”
Section: Soil Inoculationmentioning
confidence: 99%